Perceptions of diabetes patients and their caregivers regarding access to medicine in a severely constrained health system: A qualitative study in Harare, Zimbabwe. - Dudzai Mureyi; Nyaradzai Arster Katena; Tsitsi Monera-Penduka (Public Library of Science (PLoS), 2022)
Nearly half of all sub-Saharan African countries lack operational Diabetes Mellitus policies. This represents an opportunity to build reliable evidence to underpin such policies when they are eventually developed. Representing the interests of those with the experience of living with the condition in national diabetes policies is important, particularly the interests regarding medicine access, a key pillar in diabetes management. One way to achieve this representation is to publish patient perceptions. Patient perspectives are especially valuable in the context of diabetes in Sub-Saharan Africa, where much of the empirical work has focused on clinical and epidemiological questions. We therefore captured the challenges and suggestions around medicine access articulated by a population of diabetes patients and their caregivers. This was a qualitative interpretivist study based on data from focus group discussions with adult diabetes patients and their caregivers. Eight FGDs of 4-13 participants each whose duration averaged 13.35 minutes were conducted. Participants were recruited from diabetes outpatient clinics at two health facilities in Harare. One site was Parirenyatwa Hospital, the largest public referral and teaching hospital in Zimbabwe. The other was a private for-profit facility. Ethics approval was granted by the Joint Research Ethics Committee for University of Zimbabwe College of Health Sciences and the Parirenyatwa Group of Hospitals (Ref: JREC 295/18). Diabetes patients and their caregivers are interested in affordable access to medicines of acceptable form and quality with minimum effort. Yet, they often find themselves privileging one dimension of access over another e.g. prioritising affordability over acceptability. Based on participants' articulations, a sound diabetes policy should: 1. provide for financial and consumer protections, 2. regulate healthcare business practices and medicine prices, 3. provide for a responsive health workforce attentive to patient problems, 4. accord the same importance to diabetes that is accorded to communicable diseases, 5. decentralize diabetes management to lower levels of care, 6. limit wastage, corruption, bad macro-financial governance and a lack of transparency about how funding for health is used, and 7. provide support to strengthen patients' and caregivers' psychosocial networks. A diabetes policy acceptable to patients is one infused with principles of good governance, fairness, inclusiveness and humanity; characterised by: financial protection and price regulation, consumer protection, equity in the attention accorded to different diseases, decentralized service delivery, inclusion of patient voice in political decision-making, a responsive compassionate health workforce, psychosocial support for patients and their caregivers and allocative efficiency and transparency in public expenditure.